Fibroblast growth factor 21 and protein energy wasting in hemodialysis patients. Issue 6 (June 2021) - Post, Adrian; Groothof, Dion; Schutten, Joëlle C.; Kelly, Dylan; Swarte, J. Casper; Flores-Guerrero, Jose L.; van der Veen, Yvonne; Kema, Ido P.; Ozyilmaz, Akin; Enya, Ayano; Westerhuis, Ralf; Bakker, Stephan J.L.; et al.
Summary: Introduction: Protein energy wasting (PEW) is the most important risk factor for morbidity and mortality in hemodialysis patients. Inadequate dietary protein intake is a frequent cause of PEW. Recent studies have identified fibroblast growth factor 21 (FGF21) as an endocrine protein sensor. This study aims to investigate the potential of FGF21 as a biomarker for protein intake and PEW and to investigate intradialytic FGF21 changes. Methods: Plasma FGF21 was measured using an enzyme-linked immunoassay. Complete intradialytic dialysate and interdialytic urinary collections were used to calculate 24-h urea excretion and protein intake. Muscle mass was assessed using the creatinine excretion rate and fatigue was assessed using the Short Form 36 and the Checklist Individual Strength. Results: Out of 59 hemodialysis patients (65 ± 15 years, 63% male), 39 patients had a low protein intake, defined as a protein intake less than 0.9 g/kg/24-h. Patients with a low protein intake had nearly twofold higher plasma FGF21 compared to those with an adequate protein intake (FGF21 1370 [795–4034] pg/mL versus 709 [405–1077] pg/mL;P < 0.001). Higher plasma FGF21 was associated with higher odds of low protein intake (Odds Ratio: 3.18 [1.62–7.95] per doubling of FGF21; P = 0.004), independent of potential confounders. Higher plasma FGF21 was also associated with lower muscle mass (std β: −0.34 [-0.59;-0.09];P = 0.009), lower vitality (std β: −0.30 [-0.55;-0.05];P = 0.02), and more fatigue (std β: 0.32 [0.07;0.57];P = 0.01). During hemodialysis plasma FGF21 increased by 354 [71–570] pg/mL, corresponding to a 29% increase. Conclusion: Higher plasma FGF21 is associated with higher odds of low protein intake in hemodialysis patients. Secondarily, plasma FGF21 is also associated with lower muscle mass, less vitality, and more fatigue. Lastly, there is an intradialytic increase in plasma FGF21. FGF21 could be a valuable marker allowing for objective assessment of PEW.